ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN TIKET KAPAL PADA PT. PELAYANAN NASIONAL INDONESIA CABANG MAKASSAR - Utami, Rizka Putri; S, Masnawaty; Samsinar, Samsinar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
This research aims to find out and analyze the accounting system for ship ticket sales information at PT Pelayaran Nasional Indonesia (PELNI) Makassar Branch. The data in this research was collected through observation, in-depth interviews and document analysis at PT Pelni Makassar branch. The population of this research is ship ticket sales reports in the sales information accounting system, while the sample is sales reports in the form of applications taken with ticket sales data collection techniques used, namely library research and field research, while the data analysis method used is the descriptive qualitative analysis method. The results of this research show that based on the results of the research conducted by the researcher, it can be concluded that the sales accounting information system at PT. The Makassar Branch of Indonesian National Shipping (PELNI) is generally good as it has established standard operational procedures regarding ticket sales and marketing which were established in 2020. However, if you compare it with accounting standards, it is not completely good enough. To implement a sales accounting system, it is necessary to provide a clear description of the accounting system for cash receipts and disbursements so that it can be used as material for evaluation and improvement of the accounting information system in the future to create transparency and accountability.